Exploring peer emotion transmission in foreign language classrooms: A social psychological investigation using mixed methods - Shao, Kaiqi; Jiang, Anne Li; Kutuk, Gulsah; Parkinson, Brian (Studies in Second Language Learning and Teaching, 2025)
Drawing on theories of interpersonal emotion transfer (Parkinson, 2020) and the control-value theory of achievement emotions (Pekrun, 2006), the present research employed a mixed-methods approach to examine how emotions are transmitted among peers in foreign language (FL) classrooms. We collected quantitative data from 308 freshmen using self-report questionnaires and qualitative data from 18 freshmen using semi-structured interviews. Results of structural equation modeling showed that students’ perceptions of peer FL enjoyment, anxiety, and boredom were positively related to their own corresponding emotions. Both control and value appraisals partially mediated the relations between perceived peer FL enjoyment and anxiety and students’ corresponding emotions. However, value appraisal was the only significant mediator of the relation between perceived peer FL boredom and student boredom. Interview findings further supported the operation of emotion contagion and social appraisal in FL peer emotion transmission. In addition, the qualitative data revealed that perceptions of peer FL emotions may also activate students’ discordant emotions as a result of social comparison processes. The interpretation of the findings is discussed along with future directions and pedagogical implications.